Pemanfaatan TikTok Sebagai Media Informasi Baru Generasi Z - Ramdani Bur; Fitria Ayuningtyas; Munadhil Abdul Muqsith (Jurnal Komunikasi Nusantara, 2023)
This research wants to explain how TikTok has become an informative medium for Generation Z. In the Information Age, technology and the internet make it easier for people to search for information. Sharing information is easy to access through websites or social media platforms. One of the rising stars whose users are increasing is the TikTok application. This social media application for sharing videos made by Bytedance continues to improve. In 2022, based on the databox, it was recorded that its use will reach 1.4 billion users worldwide. Business of Apps data in 2021 shows that almost 60% of its users are Gen Z. TikTok has developed into a place for people to get information. In this research, the researcher explains how the phenomenon of using the TikTok application as a new information media for Generation Z is in a case study in Lagoa Village, North Jakarta. The research method is qualitative with a phenomenological approach. Data collection techniques with interviews, observation, and literature study. The research results show that TikTok has emerged as a new information medium that is popular among the public, with users using it to share knowledge, insights, and information in various fields. The TikTok application has a very high impact on society. Very high is meant here; the information obtained from the TikTok application makes people confident to act after being exposed to information that interests them. Abstrak Penelitian ini ingin menjelaskan bagaimana TikTok menjadi media Informatif kalangan Generasi Z. Era Informasi, teknologi dan internet mempermudah orang melakukan pencarian informasi. Berbagi informasi begitu mudah di akses melalui website ataupun berbagai platfom media sosial. Salah satu rising star yang meningkat penggunanya ada Aplikasi TikTok. Aplikasi media sosial untuk berbagi video besutan Bytedance ini meningkat terus. Tahun 2022, berdasarkan databoks tercatat penggunaannya mencapai1.4 Miliyar pengguna diseluruh dunia. Data Business of Apps pada 2021 memperlihatkan hampir 60% penggunanya adalah Gen Z. TikTok berkembang menjadi salah satu wadah masyarakat memdapatkan informasi. Dalam penelitian peneliti ini menjelaskan bagaimana fenomena penggunaan aplikasi TikTok sebagai media informasi baru Generasi Z di studi kasusnya di Kelurahan Lagoa, Jakarta Utara. Metode penelitian adalah kualitatif dengan pendekatan fenomenologi. Teknik pengumpulan data dengan wawancara, observasi dan studi literatur. Hasil penelitian menunjukan TikTok muncul menjadi media informasi baru yang populer di kalangan masyarakat, dengan pengguna yang memanfaatkannya untuk berbagi pengetahuan, wawasan, dan informasi dalam berbagai bidang. Aplikasi TikTok memberikan dampak yang sangat tinggi kepada masyarakat. Sangat tinggi yang dimaksud di sini, informasi yang didapat dari aplikasi TikTok membuat masyarakat yakin untuk bertindak setelah terpapar sebuah informasi yang menarik menurut mereka.